Analysis of Sharia Economic Law on Profit Sharing Practices in Infrastructure Projects: A Case Study of Mudharabah at CV. Biru Karya Pratama - Syaefryan, Najma Annisa; Sri Yuniarti , Vinna; Asro, M.; Nurfauziah Rukmini, Neng Vivie (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the application of the mudharabah contract in the Main Street Lighting Pole (PJU) project by CV. Biru Karya Pratama in the City of Bandung in the perspective of sharia economic law. The focus of the study lies in the analysis of the implementation of the principles of justice and transparency in the profit-sharing system, especially related to the conformity of the mudharabah contract with sharia provisions. A qualitative approach with a descriptive method was used to obtain data through interviews, field observations, documentation studies, and literature reviews. The findings of the study revealed that although the mudharabah contract has formally fulfilled the principles and legal conditions according to Islamic law, it was found that there was a practice of giving an additional Rp5,000,000.00 to investors outside the initial agreement. This practice has the potential to give rise to an element of gharar if it is not supported by legal clarity and written agreements. This study emphasizes that transparency in fund management and consistency with the principles of the contract are crucial elements in maintaining the validity of sharia transactions. Therefore, it is necessary to strengthen the aspects of legality and contractual clarity to avoid legal implications that are contrary to sharia economic principles.